2021
DOI: 10.1093/eurheartj/ehab618
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular immunotoxicities associated with immune checkpoint inhibitors: a safety meta-analysis

Abstract: Aims  The risk and incidence of cardiovascular (CV) immune-related adverse events (irAEs) associated with immune checkpoint inhibitors (ICIs) in cancer patients remain unknown. Methods and results We systematically reviewed all randomized clinical trials (RCTs) including at least one ICI-containing arm and available CV adverse event (CVAE) data in cancer patients in the ClinicalTrials.gov registry, Medline, and the Cochrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 42 publications
2
75
0
2
Order By: Relevance
“…In a meta-analysis of 112 trials including 19,217 patients, IRAE-associated fatality rates ranged between 0.36% for anti-PD-1 mono-therapy and 1.23% for PD1/PD-L1 plus CTLA-4 combinational therapy and were most commonly caused by colitis, pneumonitis, hepatitis, myocarditis and neurotoxic effects ( 145 ). Cardiovascular IRAEs, which include myocarditis, pericardial diseases, heart failure, dyslipidemia, myocardial infarction, and cerebral arterial ischemia, are, overall, relatively rare with an incidence ranging between ~3 and 20 per 1,000 patients ( 146 ). Yet, cardiovascular toxicities are severe in over 80% of cases ( 147 ) and myocarditis, which carries the highest fatality risk of all IRAEs (40–50%), is of particular prognostic relevance ( 145 , 147 ).…”
Section: Effects Of Clinically Approved Cancer Immunotherapies On Ath...mentioning
confidence: 99%
“…In a meta-analysis of 112 trials including 19,217 patients, IRAE-associated fatality rates ranged between 0.36% for anti-PD-1 mono-therapy and 1.23% for PD1/PD-L1 plus CTLA-4 combinational therapy and were most commonly caused by colitis, pneumonitis, hepatitis, myocarditis and neurotoxic effects ( 145 ). Cardiovascular IRAEs, which include myocarditis, pericardial diseases, heart failure, dyslipidemia, myocardial infarction, and cerebral arterial ischemia, are, overall, relatively rare with an incidence ranging between ~3 and 20 per 1,000 patients ( 146 ). Yet, cardiovascular toxicities are severe in over 80% of cases ( 147 ) and myocarditis, which carries the highest fatality risk of all IRAEs (40–50%), is of particular prognostic relevance ( 145 , 147 ).…”
Section: Effects Of Clinically Approved Cancer Immunotherapies On Ath...mentioning
confidence: 99%
“…Administration of PD-1 antibodies in these mice further increased lesional inflammation and T-cell recruitment [64]. The converse is also true; stimulation of PD-1 pathways protect against atherosclerosis by modulating T-cell activityreducing interferon-gamma producing CD4+ T cells and increasing atheroprotective Real world: 0.3-1.9% [5,55,71] Trials: 0.8% [7] a From studies with minimum of 12 months average/median follow-up.…”
Section: Atherosclerosis/arterial Thromboembolic Eventsmentioning
confidence: 99%
“…From observational studies and meta-analyses of trials, ICI therapy has been associated with an increased risk of heart failure [5,7,52]. Although the association remains unclear as studies do not have clear definitions of heart failure making it not possible to discern between worsening of preexisting chronic heart failure, development of de-novo heart failure/cardiomyopathy or undiagnosed ICI-associated myocarditis.…”
Section: Cardiac Toxicities Of Systemic Treatments In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent pharmacovigilance analysis, it was found that cardiac irAEs in the vigiAccess database were mainly associated with myocarditis ( Rubio‐Infante et al, 2021 ). Recently in a metanalysis of randomized clinical trials including 32,518 patients, the ICIs therapies were associated with an increased risk of six different cardiac irAEs including myocarditis, pericardial diseases, heart failure, dyslipidemia, myocardial infarction, and cerebral arterial ischemia with a higher risk for myocarditis development (Peto OR: 4.42, 95% CI: 1.56–12.50, p < 0.01) ( Dolladille et al, 2021 ). Despite, in a study by Agostinetto et al , neither significant differences were found in cardiac irAEs between ICI and non-ICI groups (RR 1.14, 95% CI 0.88–1.48, p = 0.326), nor between dual ICI and single ICI groups ( Agostinetto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%